Physicochemical Analysis of Pond Water Samples from Selected Areas in Valukkai Aru Drainage Channel, Jaffna, Sri Lanka - Ganeshalingam, S.; Jeyadevan, J. P.; Kuganathan, N. (ISSN, 2012)
In this paper, chemical and physical characters are analysed using standard procedures for the pond water samples collected from four ponds in Valukkai Aru, Jaffna, Sri Lanka. Properties of pond water evaluated in this analysis include pH, electrical conductivity, total solids, total hardness, salinity, total alkalinity, dissolved ammonia, dissolved oxygen etc. Based on the measurements of chemical and physical characters, the quality of the pond water is discussed for different human activities such as agriculture, industry and fishery.
Keywords: pond water; chemical analysis; salinity; hardness